Análise da relação do uso e cobertura da terra nos recursos hídricos da bacia hidrográfica do Rio Paraguaçu - Ba - Silva, Adeid Rodrigues Santos (2023)
Since the influence of land use and land cover on the maintenance of water bodies is so relevant, we sought to scientifically deepen this theme. This dissertation is built in the format of chapters, a total of four, an alternative that aims to facilitate the preparation for disclosure in the format of a scientific article. Chapter 1 contains the general presentation, the general and specific objectives, and the structure of the dissertation. Chapter 2 presents a bibliometric study to characterize the publications on land use and land cover change and the dynamics of water resources in the world. The data were obtained from the Scopus platform and analyzed in the statistical package Bibliometrix, available in the statistical programming language R, and the co-occurrence networks were constructed in the software VOSviewer. The objective of the research was to analyze, through a theoretical and methodological approach, how land use and land cover influence water resources. A total of 392 publications were selected from the period 1985-2021 with the first publication in 1990. With the research it was possible to observe that the increase in terms and approaches was gradual and accentuated according to the advancement of research, and that the theme is the subject of studies globally and knowledge is being consolidated with collaboration between different countries and organizations. Chapter 3 brings an analysis of how land use and land cover change can influence the maintenance of water bodies in the Paraguaçu River Basin. The land use and land cover data were acquired from MapBiomas and the historical flow series obtained from the river gaging stations of the hydrometeorological network of the Hydrological Information System (Hidroweb). Aiming at a better understanding of the phenomena that occurred in the study area, the basin was divided into contributing basins. In general, the expansion of irrigated agriculture, the increase in pasture areas and the decrease of forests can be directly related to the reduction of water resources in the region. Due to the current conditions of environmental degradation of the basin, the implementation of actions aimed at the recovery of its environmental quality is urgent. Finally, Chapter 4 presents the compilation of the results obtained in this work and the final and general considerations about the dissertation.